Analysis of the Effectiveness of Implementing the ASN Performance Assessment System (E-Kinerja) - Siahaan, Febri Sari; Priscillia, Amanda Sona; W. A. N, Ayi Krisnha; Hidayat, Rahmat; Restika, Dea (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Human resources (HR) play a major role in achieving organizational goals, including in the government sector. Civil Servants (PNS) as an integral part of government organizations must have high competence and integrity in order to carry out their duties optimally. This research aims to analyze the effectiveness of implementing an electronic-based performance assessment system (E-Kinerja) known as SIPENDEKAR at the Tangerang Regency Population Control and Family Planning Office. This system is expected to increase transparency, efficiency and accuracy in assessing employee performance and improve the performance allowance system. The method used in this research is a qualitative approach with data collection techniques through interviews with five ASN employees who have in-depth knowledge about the implementation of the E-Kinerja system. The research results show that the implementation of SIPENDEKAR has a positive impact in increasing employee discipline and transparency in the management of performance allowances. However, this system also faces technical problems, such as slow internet connections and server problems which affect the smooth use of the application. Apart from that, another challenge found was the mismatch between employee competency and position placement, which could affect the effectiveness of the system. However, with continuous training and increasing the match between employee duties and competencies, this system can be more optimal. Overall, implementing E-Kinerja can improve employee performance and help government agencies achieve goals more efficiently.